Implementation of Technology-Enabled Field Service Management (FSM) for Enhancing Operational Effectiveness A Case Study of PT Biner Sinergi Optima - Lambok Parulian; Rhian Indradewa; Unggul Kustiawan; Ketut Sunaryanto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid advancement of digital transformation has driven organizations across various industries to integrate information and communication technologies into their operational processes to enhance efficiency, productivity, service quality, and organizational competitiveness. Within the security services industry, challenges related to human resource management, field supervision, operational monitoring, and compliance with customer service standards remain significant issues that require innovative and technology-driven solutions. This study aims to analyze the implementation of the Smart Field Service Management (Smart-FSM) model as a digital-based operational framework for security service management at PT Biner Sinergi Optima. This research employs a qualitative descriptive approach using documentation study methods, with data derived from the company’s operational planning documents and digital transformation initiatives. The Smart-FSM model integrates several advanced technologies, including cloud computing, the Internet of Things (IoT), Artificial Intelligence (AI), Machine Learning (ML), and drone-based patrol systems, to support real-time monitoring, data-driven decision-making, and operational optimization. The findings indicate that the implementation of Smart-FSM contributes significantly to improving supervisory effectiveness, accelerating response and decision-making processes, increasing transparency in service delivery, and strengthening compliance with operational standards. Furthermore, the system supports the achievement of a minimum Service Level Agreement (SLA) target of 90%, while simultaneously reducing operational inefficiencies and associated costs. The integration of these digital technologies also provides a sustainable competitive advantage through enhanced service quality, operational reliability, and customer satisfaction. Therefore, Smart-FSM can be considered a relevant and innovative operational model to support the digital transformation agenda of the security services industry in Indonesia and improve organizational performance in an increasingly technology-oriented business environment.